The HMG-domain protein BAP111 is important for the function of the BRM chromatin-remodeling complex in vivo - Papoulas, Ophelia (The National Academy of Sciences, 2001)
The Drosophila trithorax group gene brahma (brm) encodes the ATPase subunit of a SWI/SNF-like chromatin-remodeling complex. A key question about chromatin-remodeling complexes is how they interact with DNA, particularly in the large genomes of higher eukaryotes. Here, we report the characterization of BAP111, a BRM-associated protein that contains a high mobility group (HMG) domain predicted to bind distorted or bent DNA. The presence of an HMG domain in BAP111 suggests that it may modulate interactions between the BRM complex and chromatin. BAP111 is an abundant nuclear protein that is present in all cells throughout development. By using gel filtration chromatography and immunoprecipitation assays, we found that the majority of BAP111 protein in embryos is associated with the BRM complex. Furthermore, heterozygosity for BAP111 enhanced the phenotypes resulting from a partial loss of brm function. These data demonstrate that the BAP111 subunit is important for BRM complex function in vivo.